Manas: um estudo das mensagens sociais acerca das masculinidades gays no grupo de Facebook BIV - Melhado, Rodrigo Casaut (2018)
This dissertation aimed to explore how men between the ages of 18 and 27 shared and told each other online about their masculinities in a Facebook group, observing the experience reports and the qualifications of gender, sexuality and desire contained in the publications of this group. The phenomenon of digital media is a process linked to the developments of networked societies and intensified since 1997 with the commercialization of the internet and, later, with the diffusion of smartphones that brought characteristics of mobile use, personal and constant of the media. In this sense, these online imaging communities promote traditional offline reconfigurations, and it is important to realize that online and offline continually exist in ways that feed back and determine. Therefore, my research problem was to understand how the social messages of the publications of these post-1985 young people, regarding their masculinities, displace or create ruptures in vocabularies and discourses to qualify gender, sexuality and desire in relation masculinities of male-manly. The results show that the population studied has a high level of education, are familiar with the Internet, and whose imaginaries trigger fantasies of metropolitan contexts of the Brazilian middle classes, although not all of them live in these cities. In addition, homosexuality appears less marked by shame or pathology, and the manas' masculinities are understood as a source of pride. Although the belief of this youthful culture in the idolatry of media figures was visible, BIV appears as an imagined online community that provides bonds of solidarity and emotional support to its inhabitants in a multi-centered way.